Meningkatkan Hasil Belajar Siswa dengan Metode Learning Comunity - Jaya, Putu Eka Juliana (Universitas Pendidikan Ganesha, 2020)
This study aims to analyze the implementation of community learning method to improve student learning outcomes in social science subjects at SMP Negeri 1 Denpasar. The research subjects were 48 students of class VIII F. The data used in this study were primary data and secondary data. The primary data source is class VIII C State 1st SMP Denpasar, school year 2018/2019. The research procedure was carried out by applying the community learning approach, which consisted of 2 cycles: planning, action and reflection, observation. Data collection techniques use observation, written evaluation, and documentation techniques. The results showed that: activities in classroom action research were said to be successful, where there was an increase in learning activities from a total of 45 students consisting of 25 male students and 20 female students, in the initial conditions there were 19 students or 42.22 percent complete, then increased to 36 students or 80 percent in the first cycle and finally in the second cycle to 45 students or 100 percent. There was an increase in the first cycle to 36 students or 80 percent with an average value of 78.89 and the second cycle increased to 87.78 at an average value with completeness of 100 percent.